TRIM72 exerts antitumor effects in breast cancer and modulates lactate production and MCT4 promoter activity by interacting with PPP3CA. Issue 5 (23rd March 2022) - Wang, Zheng; Li, Haixia; Wang, Hongxia; Li, Xin; Zhang, Qiong; Wang, Haifang; Li, Kui; Qiu, Yurong
Abstract : A hypoxic tumor microenvironment (TME) promotes cancer progression, yet its value as a therapeutic target remains underexploited. Tripartite motif-containing 72 (TRIM72) may protect cells against various stresses including hypoxia. Recently, low TRIM72 expression has been implicated in cancer progression. However, the biological role and molecular mechanism of TRIM72 in breast cancer (BC) remain unclear. Herein, we analyzed the TRIM72 expression in BC tissue and cell lines by western blot (WB) and quantitative reverse transcription-PCR. We established the overexpression of TRIM72 using plasmids and lentiviral-mediated upregulation, as well as downregulation of protein phosphatase 3 catalytic subunit alpha (PPP3CA) by siRNA. The tumor-suppressive roles of TRIM72 were assessed on BT549 and MDA-MB-231 cells by MTS, Transwell, and flow cytometry assays in vitro and in xenografted tumors in vivo . The molecular mechanism of TRIM72 was investigated by luciferase reporter and co-immunoprecipitation (Co-IP) assay. Lactate production was measured by ELISA under hypoxic environments induced by CoCl2 . Moreover, the expression of PI3K/Akt/mTOR pathway-associated proteins was detected by WB in BC cells. Results showed that TRIM72 was downregulated in BC. Overexpression of TRIM72 inhibited tumor proliferation and invasion in vitro and in a xenograft tumor model. Mechanistically, PPP3CA altered the inhibitory effects of TRIM72 on hypoxia-induced lactate production and monocarboxylate transporter 4-promoter activity, as well as the effect of the PI3K/Akt/mTOR signaling pathway. Our study suggests that TRIM72 modulates the TME and plays tumor-suppressive roles in BC progression. Therefore, TRIM72 may serve as a potential therapeutic target in BC.